(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes the early clinical signs of prostate adenoma in young men and the challenges of differential diagnosis with other urogenital diseases. The difficulties of early detection, the ambiguity of patients’ complaints, and the importance of accurate differentiation are discussed. Research findings indicate that in young men, prostate adenoma often mimics chronic prostatitis or functional dysuria. The necessity of comprehensive clinical, laboratory, and instrumental examinations for effective early diagnosis is emphasized.